Turkey-Russia energy relations: The limits of forging cooperation through economic interdependence - Kardas, Saban (International journal (Toronto), 2011)
The multifaceted energy relations between Turkey and Russia offer a crucial case to study the changing priorities of Turkish foreign policy and the limits of this transformation. Turkey has adopted cooperative policies based on a positive-sum logic and downplayed competitive negative-sum calculations. Within this new approach to international relations, Turkey seeks to use interdependencies forged through economic exchanges as a tool to dampen political disputes and induce positive transformation in the behaviour of its partners. The transformation of Turkish-Russian relations from adversity to managed competition and the current phase of multidimensional partnership owes a great deal to the economic interdependence imparted most crucially by energy cooperation. Turkey's pursuit of a more independent approach vis-a-vis the west and its forging of closer economic and political relations with its northern neighbour Russia are a testament to the success of its new foreign policy vision, which also values cooperation with its immediate neighbours. As this article will argue, Russia's failure to deliver on Turkey's expectations in both energy and neighbourhood issues exposes the limitations of this new approach. The return to competitive dynamics after the parties reached a historic grand bargain in energy cooperation in 2009 clearly reveals the boundaries of Turkey's positive-sum approach to energy cooperation with Russia. Adapted from the source document.